The FDM technique in processes of prototyping spare parts for servicing and repairing agricultural machines: a general outline - Łukaszewski, Krzysztof; Buchwald, Tatiana; Wichniarek, Radosław (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this research was to determine the possibility of applying alternative techniques for the production of prototypes for spare parts in agriculture and to determine the possible directions of development of their applications in the engineering industry.
Keywords: FDM (Fused Deposition Modeling); FFF (Fused Filament Fabrication); 3D printing; spare parts; agricultural machinery; cost analysis